Sarcoptic mange in the wild boar, Sus scrofa, in Sweden - Axel Sannö (Elsevier, 2021)
Sarcoptic mange caused by Sarcoptes scabiei has been present in the Swedish red fox (Vulpes vulpes) population since the 1970s. The disease has been described in other Swedish wildlife species, but not in the wild boar, Sus scrofa, until 2009. Single cases of sarcoptic mange have been diagnosed the last years in the expanding population of wild boar. This study aims to describe the histopathological lesions found on mangy wild boar and compare, by molecular methods, mites from wild boar cases with mites from mangy red foxes, raccoon dogs, and domestic pigs. Mangy wild boar with focal alopecia and clinical signs of pruritis were reported or submitted from various areas in southern Sweden to the National Veterinary Institute, Uppsala. The examined skin samples of wild boar infected with S. scabiei showed limited gross skin lesions, except for cases with severe exudative dermatitis. Histopathology of the affected wild boar skin samples showed an eosinophilic dermatitis with a variable hyperkeratosis and often low number of mites present. To study the relationship of S. scabiei mites isolated from different host species, a population genetics investigation was performed based on microsatellite markers. In total, 225 individual mites from eight individuals of four different host species; red fox (48 mites), wild boar (80 mites), domestic pig (48 mites) and raccoon dog (43 mites), were included in the study. In the phylogenetic analysis, all mites isolated from wild boar clustered together even though they originate from different geographical regions in Sweden. Mites from each individual host showed high similarity. The results indicate that wild boar mites differ from mites both from the red fox, raccoon dog, and domestic pig.